Islamic Education Thought According to KH. Hasim Asy'ari and KH. Ahmad Dahlan - Siti Wasilah; Muhtadi Abdul Mun’im (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the thought of Islamic education according to KH. Hasyim Asy'ari and KH. Ahmad Dahlan, focusing on the analysis of the similarities and differences in the educational concepts of the two figures and their relevance in the context of contemporary Islamic education. Using qualitative research methods with a content analysis and comparative approach, this study analyzes the primary works of the two figures as well as various relevant contemporary research. The results of the study show that although they have different approaches, the two figures have the same goal in the formation of a complete Muslim personality. KH. Hasyim Asy'ari emphasized strengthening the traditional values of Islamic boarding schools while remaining open to modernity, while KH. Ahmad Dahlan took a more progressive approach by integrating Islamic and modern education. The thinking of the two figures has significant relevance in facing the challenges of contemporary Islamic education, especially in terms of the balance between the.